Natural Enemies Associated with Black Parlatoria Scale, Parlatoria ziziphi (Lucas) (Homoptera: Diaspididae), in Citrus Orchards at El- Qualubia Governorate, Egypt - Faskha, Shadi Mahmoud (ENTOMOLOGIA HELLENICA, 2021)
A survey on black parlatoria scale, Parlatoria ziziphi (Lucas), natural enemies present at El-Qualubia Governorate, Egypt, during the season 2010-2011, was carried out in an orchard of navel orange. Identification of the collected samples indicated that the most abundant enemies were the ectoparasitoid Aphytis hispanicus (Mercet), the endoparasitoid Prospaltella inquirenda (Silvestri) and two predatory mites Cheletogenes ornatus (Canestrini&Fanzago) and Amblyseius swirskii (Athias-Henriot). Aphytis hispanicus preferred to parasitize on males more than females and nymphs, whereas P. inquirenda preferred to attack females more than males and nymphs. The activity of parasitoids was not observed during the two main periods, the first from July to August, and the second from January to March. On the other hand, the predatory mites, C. ornatus and A. swirskii, prefer nutrition to females more than males and nymphs. The percentage of their population was high during the winter-spring and autumn host generations.